Comparative effects of salt and alkali stress on photosynthesis and root physiology of oat at anthesis - Qin, Yan; Bai, Jianhui; Wang, Yuqing; Liu, Jinghui; Hu, Yongning; Dong, Zhi; Ji, Lei (Archives of Biological Sciences, 2018)
The effects of different concentrations of salt and alkali on root physiology and photosynthesis in oat (Avena sativa L.) at anthesis were compared. Treatment with salt and particularly with alkali, decreased yield and grain weight. Both alkali and salt treatments decreased the photosynthetic rate (Pn), stomatal conductance and chlorophyll content, with the effect on Pn and the chlorophyll content more marked after treatment with alkali. The decrease in Pn induced by salt and mild alkali (50 mmol L-1) contributed to a decrease in stoma opening. Under moderate and severe concentrations of alkali (100 and 150 mmol L-1 respectively), other factors rather than stoma closure were responsible for limiting Pn. The transpiration rates (Tr) in alkali-treated plants were higher than in salt-treated plants. We also observed decreases in both root volume and root dry weight, and increases in root activity in alkali- and salt-treated plants. Severe alkali and salt concentrations (150 mmol L-1) decreased the root-shoot ratio. A positive correlation between yield and root dry weight and a negative correlation between root activity and Pn were observed. Alkali and salt treatments increased superoxide dismutase (SOD) and peroxidase (POD) activities and the malondialdehyde (MDA) content, but decreased catalase (CAT) activity. Yield was negatively correlated with MDA, and the MDA content was greater under alkali treatments than after salt treatment. We conclude that alkali treatments had more severe effects on oat plants at anthesis than salt treatments. https://doi.org/10.2298/ABS171124050Q Received: July 10, 2017; Revised: November 24, 2017; Accepted: November 25, 2017; Published online: November 29, 2017 How to cite this article: Qin Y, Bai J, Wang Y, Liu J, Hu Y, Dong Z, Ji L. Comparative effects of salt and alkali stress on photosynthesis and root physiology of oat at anthesis. Arch Biol Sci. 2018;70(2):329-38.